Evaluasi Daya Dukung Perkerasan Apron terhadap Pesawat Airbus 330-300 Dengan Metode FAA - Akmal, Mohammad Zaki; Surachman, Luky (Jurnal Teknik Transportasi, 2024)
The apron pavement at airports plays an important role in supporting the weight of aircraft and ensuring safety. This research aims to evaluate the carrying capacity of rigid apron pavement against the load of Airbus 330-300 aircraft, which are the most critical aircraft. The FAA method is used as the basis for analyzing the bearing capacity of pavement in this research. This FAA method is a method that has been recognized and is widely used in planning apron pavement at airports. Specifications for apron pavement at airports which are the focus of research. Airbus 330-300 aircraft load data, including maximum take-off weight, was obtained from reliable sources. The analysis is carried out by considering main parameters such as the number of annual aircraft movements, type and weight of aircraft in operation. FAARFIELD is used to design pavement thickness while COMFAA calculates pavement thickness evaluation with the final results of PCN and ACN values. Based on the calculations, the PCN > ACN value is obtained. The PCN value is 94 and the ACN value is 75. Based on this evaluation, it can be concluded that the rigid apron at Adi Soemarmo International Airport can accommodate the load of an Airbus 330-300. Keywords: apron pavement, aircraft load, airbus 330-300, FAA method